MAKE HAPPINESS A PRIORITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
In this day and age, uncertainties have become as common as the global weather patterns. Brickbats and broomsticks are part of today’s social interaction, as society becomes more competitive, while giving passing criticisms and being judgemental seem to be in the repertoire of many.